Hyperbius joceliae a new species of Ditomotarsinae from Tierra del Fuego, Argentina (Hemiptera: Acanthosomatidae) - Carpintero, Diego Leonardo; de Biase, Sebastián (Zootaxa, 2021)
Hyperbius joceliae sp. n., a new Patagonian Acanthosomatidae (Hemiptera) species is described from the north of Tierra del Fuego Island. Diagnostic characters such as color, dorsal pilosity, head and pronotal punctures, length of mandibular plates and antennae, shape and color of paratergite 9, shape and texture of gonocoxite I and II of the only known species of the genus, Hyperbius geniculatus (Signoret), are compared with the new species and discussed. Distributional patterns of the South American Acanthosomatidae and speciation of the Patagonian fauna of this family are also briefly discussed.